Cerebroplacental versus Umbilicocerebral Ratio—Analyzing the Predictive Value Regarding Adverse Perinatal Outcomes in Low- and High-Risk Fetuses at Term - Stumpfe, Florian; Mayr, Andreas; Schneider, Michael; Kehl, Sven; Stübs, Frederik; Antoniadis, Sophia; Titzmann, Adriana; Pontones, Constanza; Bayer, Christian M.; Beckmann, Matthias; Faschingbauer, Florian (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate the prediction of adverse perinatal outcomes using the cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in different cohorts of singleton pregnancies. Materials and Methods: In this retrospective cohort study, we established our own Multiple of Median (MoM) for CPR and UCR. The predictive value for both ratios was studied in the following outcome parameters: emergency cesarean delivery, operative intervention (OI), OI due to fetal distress, 5-min Apgar < 7, admission to neonatal intensive care unit, and composite adverse perinatal outcome. The performance of the ratios was assessed in the following cohorts: total cohort (delivery ≥ 37 + 0 weeks gestation, all birth weight centiles), low-risk cohort (delivery ≥ 37 + 0 weeks gestation, birth weight ≥ 10. centile), prolonged pregnancy cohort (delivery ≥ 41 + 0 weeks gestation, birth weight ≥ 10. centile) and small-for-gestational-age fetuses (delivery ≥ 37 + 0 weeks gestation, birth weight < 10. centile). The underlying reference values for MoM were estimated using quantile regression depending on gestational age. Prediction performance was evaluated using logistic regression models assessing the corresponding Brier score, combining discriminatory power and calibration. Results: Overall, 3326 cases were included. Across all cohorts, in the case of a significant association between a studied outcome parameter and CPR, there was an association with UCR, respectively. The Brier score showed only minimal differences for both ratios. Conclusions: Our study provides further evidence regarding predictive values of CPR and UCR. The results of our study suggest that reversal of CPR to UCR does not improve the prediction of adverse perinatal outcomes.
CRIS-Team Scopus Importer:2023-09-08
Keywords: cerebroplacental ratio; CPR; UCR; umbilicocerebral ratio

Digital Maternity Records: Motivation, Acceptance, Requirements, Usability and Prototype Evaluation of an Interface for Physicians and Midwives - Dörflinger, Luisa; Nissen, Michael; Jäger, Katharina; Wirth, Markus; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (Mensch und Computer 2021, 2021)
Maternity records (”Mutterpass”) are a central tool in Germany’s antenatal care. Its digitalisation offers advantages such as improved readability, data standardisation, analysability, digital assistance and the avoidance of media breaks. Despite the examined necessity and technical possibility, no system has been implemented yet. In this work, we address this gap by assessing physicians’ and midwives’ perception, motivation, acceptance and requirements of a digital maternity record and its user interface in particular. Nine medical professionals participated in semi-structured interviews. Based on the results, an interface prototype was subsequently developed. The prototype laid a particular focus on two different gravidogram implementations. Thirteen medical professionals participated in the interactive user interface study, which aimed to assess general acceptance, completion time, error rate and implemented assistance functions compared to the analogue counterpart. Results show that the implementation of the digital maternity logbook is of value and that its advantages are both accepted and demanded by medical professionals. Eight key requirements were identified. A tabular gravidogram prototype, inspired by the analogue maternity record, was favoured over a more novel list prototype. Users presented a clear learning curve of the digital system. Nevertheless, the digital average completion time is 30% higher than its analogue counterpart. The digital prototype lead to a lower average number of errors per entry (0.45±0.3 vs. 0.58±0.4). With respect to digital maternity records, this work underlines user acceptance, summarizes key user requirements and presents a first step on the path to a digital maternity record interface for medical professionals. On a broader scale, it delivers insights based on several metrics with respect to digitalisation in an area that is still highly dominated by long established paper-based tools.

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of prenatal alcohol exposition on cognitive outcomes in childhood and youth: a longitudinal analysis based on meconium ethyl glucuronide. - Roetner, Jakob; Van Doren, Jessica; Maschke, Janina; Kulke, Louisa; Pontones, Constanza; Fasching, Peter A.; Beckmann, Matthias W.; Lenz, Bernd; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (European archives of psychiatry and clinical neuroscience, 2024)
BACKGROUND: Prenatal alcohol exposure (PAE) has been linked to severe, adverse child outcomes. However, little is known regarding subclinical outcomes of low/moderate PAE and its longitudinal consequences, especially regarding neurophysiological and neurocognitive development. A newborn biomarker of PAE, meconium ethyl glucuronide (EtG), has been shown to predict cognitive impairments in primary-school-aged children. The current study investigated the ongoing effects of subclinical PAE in adolescence. METHODS: A sample of n = 96 mother-child dyads of the FRAMES/FRANCES cohort were classified into PAE/no PAE using EtG with a 10 ng/g cutoff. Mothers were recruited during pregnancy and children were assessed during primary-school age (M = 7.57, SD = 0.65, range: 6.00-9.92 years) and adolescence (M = 13.26, SD = 0.31, range: 12.79-14.20 years) on three levels: clinical (ADHD rating), neuropsychological (IQ score and performance in a go/nogo task), and neurophysiological (analysis of P3 event-related potentials (ERP) during said go/nogo task). Developmental outcomes and courses following PAE were assessed using rmANCOVAs, controlling for relevant confounders (socioeconomic status (SES), birth weight, and maternal psychopathology). RESULTS: Neurophysiological impairments emerged for exposed children in the form of diminished attentional resource recruiting in childhood and adolescence (reduced go-P3 amplitudes) with no differences in performance. Neuropsychological testing showed a reduced IQ score for both time points with dose-dependent effects in childhood. Clinical ADHD symptoms were not significantly affected. CONCLUSION: Subclinical PAE, as determined by meconium EtG, has negative developmental consequences on cognitive function that persist from childhood to adolescence. These findings suggest that there is no safe limit for alcohol consumption during pregnancy and that more thorough screening of alcohol consumption during pregnancy is necessary for early identification and treatment of at-risk children.
EVALuna2:538816

Feasibility and Acceptance of Self-Guided Mobile Ultrasound among Pregnant Women in Routine Prenatal Care - Pontones, Constanza; Titzmann, Adriana; Hübner, Hanna; Danzberger, Nina; Rübner, Matthias; Häberle, Lothar; Eskofier, Björn; Nissen, Michael; Kehl, Sven; Faschingbauer, Florian; Beckmann, Matthias; Fasching, Peter; et al. (Journal of Clinical Medicine, 2023)
Background and objectives: Mobile and remote ultrasound devices are becoming increasingly available. The benefits and possible risks of self-guided ultrasound examinations conducted by pregnant women at home have not yet been well explored. This study investigated aspects of feasibility and acceptance, as well as the success rates of such examinations. Methods: In this prospective, single-center, interventional study, forty-six women with singleton pregnancies between 17 + 0 and 29 + 6 weeks of gestation were included in two cohorts, using two different mobile ultrasound systems. The participants examined the fetal heartbeat, fetal profile and amniotic fluid. Aspects of feasibility and acceptance were evaluated using a questionnaire. Success rates in relation to image and video quality were evaluated by healthcare professionals. Results: Two thirds of the women were able to imagine performing the self-guided examination at home, but 87.0% would prefer live support by a professional. Concerns about their own safety and that of the child were expressed by 23.9% of the women. Success rates for locating the target structure were 52.2% for videos of the fetal heartbeat, 52.2% for videos of the amniotic fluid in all four quadrants and 17.9% for videos of the fetal profile. Conclusion: These results show wide acceptance of self-examination using mobile systems for fetal ultrasonography during pregnancy. Image quality was adequate for assessing the amniotic fluid and fetal heartbeat in most participants. Further studies are needed to determine whether ultrasound self-examinations can be implemented in prenatal care and how this would affect the fetomaternal outcome.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acceptance; feasibility; mobile ultrasound; pregnancy; prenatal care; self-guided ultrasound

Hormonphobie: Wie kann ich sicherere Verhütungsmethoden beraten? - Pontones, Constanza; Oppelt, Patricia (gynäkologische praxis, 2021)
Many women are currently dissatisfied with their choice of contraception. The fear, mood could be changed or the feeling of being controlled by others is leading more and more women to abandon their safe hormonal contraception and use unsafe methods of contraception. In current surveys, the desire for individual and comprehensive contraception advice is growing. Especially young women pose a challenge in contraception advice, as they confront us with many information from the internet and wish an individual and personal contraception advice. Based on specific questions addressed to the patient, the optimal method of contraception can be found. Additionally, these questions should be repeated at regular intervals to find out if the current contraception method is still suitable.
CRIS-Team Scopus Importer:2024-12-16
Keywords: contraception; contraception advice; hormonal contraception; hormone phobia

Kontrazeption – neue Trends, auch für Jugendliche - Pontones, Constanza; Oppelt, Patricia (Pädiatrische Praxis, 2023)
Contraception advice for girls and young women is becoming more and more challenging as information from the internet increases. Although great importance is attached to reliable contraception, there is currently a shift from safe to non-safe contraceptive methods. More than half of the young women would like to change their contraceptive method. Both the new combination of estetrol/drospirenone and the new estrogen-free pill consisting of drospirenone are a good addition to the currently available hormonal contraceptives due to their favorable profile of effects. A good contraceptive advice is needed to find the optimal contraceptive method, taking into account the individual risk profile and the desired additional side effects.
CRIS-Team Scopus Importer:2024-12-16
Keywords: contraceptive counseling for adolescents; hormone phobia; new hormonal contraceptives

Longitudinal Course of Short-Term Variation and Doppler Parameters in Early Onset Growth Restricted Fetuses - Baier, Friederike; Weinhold, Leonie; Stumpfe, Florian; Kehl, Sven; Pretscher, Jutta; Bayer, Christian M.; Topal, Nalan; Pontones, Constanza; Mayr, Andreas; Schild, Ralf Lothar; Schmid, Matthias; Beckmann, Matthias; et al. (Ultraschall in der Medizin, 2019)
PURPOSE: To evaluate the longitudinal pattern of fetal heart rate short term variation (STV) and Doppler indices and their correlation to each other in severe growth restricted (IUGR) fetuses. MATERIALS AND METHODS: In this retrospective study, pregnancies with a birth weight below the 10th percentile, born between 24 and 34 gestational weeks with serial Doppler measurements in combination with a computerized CTG (cCTG) with calculated STV were included. Longitudinal changes of both Doppler indices and STV values were evaluated with generalized additive models, adjusted for gestational age and the individual. For all measurements the frequency of abnormal values with regard to the time interval before delivery and Pearson correlations between Doppler indices and STV values were calculated. RESULTS: 41 fetuses with a total of 1413 observations were included. Over the course of the whole study period, regression analyses showed no significant change of STV values (p = 0.38). Only on the day of delivery, a prominent decrease was observed (mean STV d28-22: 7.97 vs. mean STV on day 0: 6.8). Doppler indices of UA and MCA showed a continuous, significant deterioration starting about three weeks prior to delivery (p = 0.007; UA and p < 0.001, MCA). Correlation between any Doppler index and STV values was poor. CONCLUSION: Fetal heart rate STV does not deteriorate continuously. Therefore, cCTG monitoring should be performed at least daily in these high-risk fetuses. Doppler indices of umbilical artery (UA) and middle cerebral artery (MCA), however, showed continuous deterioration starting about 3 weeks prior to delivery.
EVALuna2:212318

Management of Uterus bicornis unicollis with a right-sided Outflow Obstruction in a 13-year-old Girl - Lubrich, Hannah; Pontones, Constanza; Koch, Matthias; Fahlbusch, C.; Oppelt, Patricia; Beckmann, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Menstrual disorders in adolescents Blutungsstörungen in der Jugendgynäkologie - Oppelt, Patricia; Lubrich, Hannah; Pontones, Constanza (gynäkologische praxis, 2021)
Menstrual disorders are often the first reason for a young woman to visit a gynecological practice. In order to ensure sensitive, age-appropriate treatment, it is important to have basic knowledge of pubertal development and normal variations of it, as well as of suitable examination techniques for girls. This article aims to establish a schematic system for amenorrhea and its various causes, in order to allow simple basic diagnostic procedures. This can make it possible to clarify findings in girls with amenorrhea in a targeted manner with little diagnostic effort. Particularly in the case of amenorrhea, further examinations often follow in order to narrow down the possible causes. Such examinations should then be carried out by experienced pediatric gynecologists. Dysmenorrhea due to endometriosis and other causes is widespread and often still goes unrecognized. Regardless of the reason for presentation, it is therefore important to actively mention dysmenorrhea to young women in order to explain the treatment options available, which may also be conservative. This can make a simple but very useful contribution to helping girls get a good start in experiencing the menstrual cycle.
CRIS-Team Scopus Importer:2024-12-16
Keywords: amenorrhea; dysfunctional uterine bleeding; dysmenorrhea; menstrual disorder

N(1)-methylnicotinamide as an endogenous probe for drug interactions by renal cation transporters: studies on the metformin-trimethoprim interaction - Mueller, Fabian; Pontones, Constanza; Renner, Bertold; Mieth, Maren; Hoier, Eva; Auge, Daniel; Maas, Renke; Zolk, Oliver; Fromm, Martin (European Journal of Clinical Pharmacology, 2015)
N(1)-methylnicotinamide (NMN) was proposed as an in vivo probe for drug interactions involving renal cation transporters, which, for example, transport the oral antidiabetic drug metformin, based on a study with the inhibitor pyrimethamine. The role of NMN for predicting other interactions with involvement of renal cation transporters (organic cation transporter 2, OCT2; multidrug and toxin extrusion proteins 1 and 2-K, MATE1 and MATE2-K) is unclear.We determined inhibition of metformin or NMN transport by trimethoprim using cell lines expressing OCT2, MATE1, or MATE2-K. Moreover, a randomized, open-label, two-phase crossover study was performed in 12 healthy volunteers. In each phase, 850 mg metformin hydrochloride was administered p.o. in the evening of day 4 and in the morning of day 5. In phase B, 200 mg trimethoprim was administered additionally p.o. twice daily for 5 days. Metformin pharmacokinetics and effects (measured by OGTT) and NMN pharmacokinetics were determined.Trimethoprim inhibited metformin transport with K i values of 27.2, 6.3, and 28.9 ?M and NMN transport with IC50 values of 133.9, 29.1, and 0.61 ?M for OCT2, MATE1, and MATE2-K, respectively. In the clinical study, trimethoprim increased metformin area under the plasma concentration-time curve (AUC) by 29.5 % and decreased metformin and NMN renal clearances by 26.4 and 19.9 %, respectively (p <= 0.01). Moreover, decreases of NMN and metformin renal clearances due to trimethoprim correlated significantly (r S = 0.727, p = 0.010).These data on the metformin-trimethoprim interaction support the potential utility of N(1)-methylnicotinamide as an endogenous probe for renal drug-drug interactions with involvement of renal cation transporters.
EVALuna2:8519

Preconceptual Counseling, Prenatal Care and peripartum Management of Female Patients with Ullrich-Turner Syndrome and a High-risk cardiovascular Profile - Pontones, Constanza; Lubrich, Hannah; Schwenke, E.; Cupisti, Susanne; Dittrich, Ralf; Kehl, Sven; Beckmann, Matthias; Fahlbusch, C.; Oppelt, Patricia (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Pregnant and Postpartum Women Requiring Intensive Care Treatment for COVID-19—First Data from the CRONOS-Registry - Sitter, Magdalena; Pecks, Ulrich; Rüdiger, Mario; Friedrich, Sabine; Malfertheiner, Sara Fill; Hein, Alexander; Königbauer, Josefine T.; Becke-Jakob, Karin; Zöllkau, Janine; Ramsauer, Babett; Rathberger, Katharina; Pontones, Constanza; et al. (Journal of Clinical Medicine, 2022)
(1) Background: Data on coronavirus 2 infection during pregnancy vary. We aimed to describe maternal characteristics and clinical presentation of SARS-CoV-2 positive women requiring intensive care treatment for COVID-19 during pregnancy and postpartum period based on data of a comprehensive German surveillance system in obstetric patients. (2) Methods: Data from COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS), a prospective multicenter registry for SARS-CoV-2 positive pregnant women, was analyzed with respect to ICU treatment. All women requiring intensive care treatment for COVID-19 were included and compared regarding maternal characteristics, course of disease, as well as maternal and neonatal outcomes. (3) Results: Of 2650 cases in CRONOS, 101 women (4%) had a documented ICU stay. Median maternal age was 33 (IQR, 30–36) years. COVID-19 was diagnosed at a median gestational age of 33 (IQR, 28–35) weeks. As the most invasive form of COVID-19 treatment interventions, patients received either continuous monitoring of vital signs without further treatment requirement (n = 6), insufflation of oxygen (n = 30), non-invasive ventilation (n = 22), invasive ventilation (n = 28), or escalation to extracorporeal membrane oxygenation (n = 15). No significant clinical differences were identified between patients receiving different forms of ventilatory support for COVID-19. Prevalence of preterm delivery was significantly higher in women receiving invasive respiratory treatments. Four women died of COVID-19 and six fetuses were stillborn. (4) Conclusions: Our cohort shows that progression of COVID-19 is rare in pregnant and postpartum women treated in the ICU. Preterm birth rate is high and COVID-19 requiring respiratory support increases the risk of poor maternal and neonatal outcome.
CRIS-Team Scopus Importer:2022-02-04
Keywords: ARDS; COVID-19; Maternal critical care; Obstetrics; Pregnancy; SARS-CoV-2

Smartphone-Based Colorimetric Analysis of Urine Test Strips for At-Home Prenatal Care - Flaucher, Madeleine; Nissen, Michael; Jäger, Katharina; Titzmann, Adriana; Pontones, Constanza; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (IEEE Journal of Translational Engineering in Health and Medicine, 2022)
Objective: Clinical urine tests are a key component of prenatal care. As of now, urine test strips are evaluated through a time consuming, often error-prone and operator-dependent visual color comparison of test strips and reference cards by medical staff. Methods and procedures: This work presents an automated pipeline for urinalysis with urine test strips using smartphone camera images in home environments, combining several image processing and color combination techniques. Our approach is applicable to off-the-shelf test strips in home conditions with no additional hardware required. For development and evaluation of our pipeline we collected image data from two sources: i) A user study (26 participants, 150 images) and ii) a lab study (135 images). Results: We trained a region-based convolutional neural network that is able to detect the urine test strip location and orientation in images with a wide variety of light conditions, backgrounds and perspectives with an accuracy of 85.5%. The reference card can be robustly detected through a feature matching approach in 98.6% of the images. Color comparison by Hue channel (0.81 F1-Score), Matching factor (0.80 F1-Score) and Euclidean distance (0.70 F1-Score) were evaluated to determine the urinalysis results. Conclusion: We show that an automated smartphone-based colorimetric analysis of urine test strips in a home environment is feasible. It facilitates examinations and provides the possibility to shift care into an at-home environment. Clinical impact: The findings demonstrate that routine urine examinations can be transferred into the home environment using a smartphone. Simultaneously, human error is avoided, accuracy is increased and medical staff is relieve

Smartphone pregnancy apps: systematic analysis of features, scientific guidance, commercialization, and user perception - Nissen, Michael; Huang, Shih-Yuan; Jäger, Katharina; Flaucher, Madeleine; Titzmann, Adriana; Bleher, Hannah; Pontones, Constanza; Hübner, Hanna; Danzberger, Nina; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (BMC Pregnancy and Childbirth, 2024)
Background Over 50% of pregnant women use pregnancy applications (apps). Some app s lack credibility, information accuracy, and evidence-based clinical advice, containing potentially harmful functionality. Previous studies have only conducted a limited analysis of pregnancy app functionalities, expert involvement/evidence-based content, used commercialization techniques, and user perception. Methods We used the keyword “pregnancy” to scrape (automatically extract) apps and app information from Apple App Store and Google Play. Unique functionalities were derived from app descriptions and user reviews. App descriptions were screened for evidence-based content and expert involvement, and apps were subsequently analyzed in detail. Apps were opened and searched for used commercialization techniques, such as advertisements or affiliate marketing. Automated text analysis (natural language processing) was used on app reviews to assess users’ perception of evidence-based content/expert involvement and commercialization techniques. Results In total, 495 apps were scraped. 226 remained after applying exclusion criteria. Out of these, 36 represented 97%/88% of the total market share (Apple App Store/Google Play), and were thus considered for review. Overall, 49 distinct functionalities were identified, out of which 6 were previously unreported. Functionalities for fetal kick movement counting were found. All apps are commercial. Only 15 apps mention the involvement of medical experts. 10.3% of two-stars user reviews include commercial topics, and 0.6% of one-/two-/three-/five stars user reviews include references to scientific content accuracy. Conclusion Problematic features and inadequate advice continue to be present in pregnancy apps. App developers should adopt an evidence-based development approach and avoid implementing as many features as possible, potentially at the expense of their quality or over-complication (“feature creep”). Financial incentives, such as grant programs, could support adequate content quality. Caregivers play a key role in pregnant individuals’ decision-making, should be aware of potential dangers, and could guide them to trustworthy app

Smart sensing in pregnancy: a survey-based evaluation of readiness to use wearable sensory applications in prenatal care - Weidenthaler, Filip; Danzberger, Nina; Pontones, Constanza; Titzmann, Adriana; Hein, Alexander; Beckmann, Matthias; Fasching, Peter; Huebner, H. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Systematic Comparison of ECG Delineation Algorithm Performance on Smartwatch Data - Jäger, Katharina; Nissen, Michael; Flaucher, Madeleine; Graf, Luisa; Joanidopoulos, Joana; Anneken, Lars; Hübner, Hanna; Goossens, Chloe; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; et al. (IEEE Access, 2024)
Cardiovascular diseases are the leading cause of global mortality, necessitating early detection and continuous monitoring for timely interventions. Smartwatches with electrocardiogram (ECG) recording capabilities enable real-time, at-home cardiac monitoring. Specific ECG characteristics can provide insights into cardiovascular diseases. The delineation of ECGs, which is the identification of fiducial points (such as onsets, offsets, and peaks), is a time-consuming task. Automated ECG delineation can enhance this process, but existing research comparing available algorithms is limited. Furthermore, to the best of our knowledge, none have addressed single-lead ECGs from smartwatches, which can be noisy and unfiltered. Thus, this study evaluates the best-performing open-source algorithm for single-lead and smartwatch ECG data. We used two public datasets (Lobachevsky University Database, QT Database) and two smartwatch datasets (SmartHeartWatch Dataset, SMART Start Dataset) including two devices (AppleWatch, Withings ScanWatch). Algorithms from three toolkits (NeuroKit, ECGKit, ECGdeli) were assessed based on the time deviation between algorithm outputs and reference annotations, sensitivity, true positives, and false negatives. Results were further evaluated against the Common Standards for Quantitative Electrocardiography (CSE) recommendations. ECGdeli outperformed the other algorithms. For QRS on- and offset, ECGkit shows comparable sensitivity, but otherwise lower scores. NeuroKit consistently shows lower sensitivity across all four data sets, however, the temporal deviation between detected point and reference was higher. Overall, sensitivity scores were higher for Apple Watch data compared to Withings ScanWatch data. This study demonstrates that segmentation algorithms are applicable to single-lead smartwatch ECG data, with ECGdeli being the most stable overall, and NeuroKit recommended for scenarios prioritizing the temporal accuracy of detected points.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Cardiovascular Diseases; ECG Segmentation; Mobile Health; Wearable Devices

Update Breast Cancer 2019 Part 3 - Current Developments in Early Breast Cancer: Review and Critical Assessment by an International Expert Panel - Kolberg, Hans Christian; Schneeweiss, Andreas; Fehm, Tanja N.; Wöckel, Achim; Huober, Jens; Pontones, Constanza; Titzmann, Adriana; Belleville, Erik; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Taran, Florin Andrei; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of breast cancer patients in a curative situation is special in many ways. The local therapy with surgery and radiation therapy is a central aspect of the treatment. The complete elimination of tumour cells at the site of the primary disease must be ensured while simultaneously striving to keep the long-term effects as minor as possible. There is still focus on the continued reduction of the invasiveness of local therapy. With regard to systemic therapy, chemotherapies with taxanes, anthracyclines and, in some cases, platinum-based chemotherapies have become established in the past couple of decades. The context for use is being continually further defined. Likewise, there are questions in the case of antihormonal therapy which also still need to be further defined following the introduction of aromatase inhibitors, such as the length of therapy or ovarian suppression in premenopausal patients. Finally, personalisation of the treatment of early breast cancer patients is also being increasingly used. Prognostic tests could potentially support therapeutic decisions. It must also be considered how the possible use of new therapies, such as checkpoint inhibitors and CDK4/6 inhibitors could look in practice once study results in this regard are available. This overview addresses the backgrounds on the current votes taken by the international St. Gallen panel of experts in Vienna in 2019 for current questions in the treatment of breast cancer patients in a curative situation.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adjuvant therapy; early breast cancer; neoadjuvant therapy; St. Gallen panel of experts

Update Breast Cancer 2019 Part 3 - Current Developments in Early Breast Cancer: Review and Critical Assessment by an International Expert Panel Update Mammakarzinom 2019 Teil 3 - aktuelle Entwicklungen bei der kurativen Behandlung von Mammakarzinom-Patientinnen: Eine Übersicht und Bewertung durch ein internationales Expertenpanel - Kolberg, Hans Christian; Schneeweiss, Andreas; Fehm, Tanja N.; Wöckel, Achim; Huober, Jens; Pontones, Constanza; Titzmann, Adriana; Belleville, Erik; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Taran, Florin Andrei; et al. (TumorDiagnostik & Therapie, 2019)
The treatment of breast cancer patients in a curative situation is special in many ways. The local therapy with surgery and radiation therapy is a central aspect of the treatment. The complete elimination of tumour cells at the site of the primary disease must be ensured while simultaneously striving to keep the long-term effects as minor as possible. There is still focus on the continued reduction of the invasiveness of local therapy. With regard to systemic therapy, chemotherapies with taxanes, anthracyclines and, in some cases, platinum-based chemotherapies have become established in the past couple of decades. The context for use is being continually further defined. Likewise, there are questions in the case of antihormonal therapy which also still need to be further defined following the introduction of aromatase inhibitors, such as the length of therapy or ovarian suppression in premenopausal patients. Finally, personalisation of the treatment of early breast cancer patients is also being increasingly used. Prognostic tests could potentially support therapeutic decisions. It must also be considered how the possible use of new therapies, such as checkpoint inhibitors and CDK4/6 inhibitors could look in practice once study results in this regard are available. This overview addresses the backgrounds on the current votes taken by the international St. Gallen panel of experts in Vienna in 2019 for current questions in the treatment of breast cancer patients in a curative situation.
CRIS-Team Scopus Importer:2019-09-17
Keywords: adjuvant therapy; early breast cancer; neoadjuvant therapy; St. Gallen panel of experts

Usability and Perception of a Wearable-Integrated Digital Maternity Record App in Germany: User Study - Nissen, Michael; Perez, Carlos A.; Jäger, Katharina; Bleher, Hannah; Flaucher, Madeleine; Hübner, Hanna; Danzberger, Nina; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; Eskofier, Björn; et al. (JMIR Pediatrics and Parenting, 2023)
Background: Although digital maternity records (DMRs) have been evaluated in the past, no previous work investigated usability or acceptance through an observational usability study. Objective: The primary objective was to assess the usability and perception of a DMR smartphone app for pregnant women. The secondary objective was to assess personal preferences and habits related to online information searching, wearable data presentation and interpretation, at-home examination, and sharing data for research purposes during pregnancy. Methods: A DMR smartphone app was developed. Key features such as wearable device integration, study functionalities (eg, questionnaires), and common pregnancy app functionalities (eg, mood tracker) were included. Women who had previously given birth were invited to participate. Participants completed 10 tasks while asked to think aloud. Sessions were conducted via Zoom. Video, audio, and the shared screen were recorded for analysis. Task completion times, task success, errors, and self-reported (free text) feedback were evaluated. Usability was measured through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). Semistructured interviews were conducted to explore the secondary objective. Results: A total of 11 participants (mean age 34.6, SD 2.2 years) were included in the study. A mean SUS score of 79.09 (SD 18.38) was achieved. The app was rated “above average” in 4 of 6 UEQ categories. Sixteen unique features were requested. We found that 5 of 11 participants would only use wearables during pregnancy if requested to by their physician, while 10 of 11 stated they would share their data for research purposes. Conclusions: Pregnant women rely on their medical caregivers for advice, including on the use of mobile and ubiquitous health technology. Clear benefits must be communicated if issuing wearable devices to pregnant women. Participants that experienced pregnancy complications in the past were overall more open toward the use of wearable devices in pregnancy. Pregnant women have different opinions regarding access to, interpretation of, and reactions to alerts based on wearable data. Future work should investigate personalized concepts covering these aspects.
Created from Fastlane, Scopus look-up
Keywords: app; application; applications; apps; attitude; attitudes; data sharing; develop; development; digital; electronic; electronic maternity record; experience; experiences; feature; features; health record; health records; information behavior; information behaviour; information seeking; log; logbook; maternal; maternity; maternity log; maternity logbook; maternity record; mHealth; mobile health; online search; opinion; opinions; paper hand-held record; perception; perceptions; personal health record; perspective; perspectives; PHR; pregnancy; pregnancy app; pregnancy record; pregnant; privacy; searching; smartphone; smartphones; usability; wearable; wearables

Veranstaltungsbericht – Rückblick auf die Summer School für Gynäkologie und Geburtshilfe an der Universitätsfrauenklinik Erlangen - Zahn, Anna; Titzmann, Adriana; Pontones, Constanza (Geburtshilfe und Frauenheilkunde, 2022)
CRIS-Team WoS Importer:2022-11-04

WebPPG: Feasibility and Usability of Self-Performed, Browser-Based Smartphone Photoplethysmography - Nissen, Michael; Flaucher, Madeleine; Jäger, Katharina; Hübner, Hanna; Danzberger, Nina; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Smartphones enable and facilitate biomedical studies as they allow the recording of various biomedical signals, including photoplethysmograms (PPG). However, user engagement rates in mobile health studies are reduced when an application (app) needs to be installed. This could be alleviated by using installation-free web apps. We evaluate the feasibility of browser-based PPG recording, conducting the first usability study on smartphone-based PPG. We present an at-home study using a web app and library for PPG recording using the rear camera and flash. The underlying library is freely made available to researchers. 25 Android users participated, using their own smartphones. The study consisted of a demographic and anamnestic questionnaire, the signal recording itself (60 s), and a consecutive usability questionnaire. After filtering, heart rate was extracted (14/17 successful), signal-to-noise ratios assessed (0.64 ± 0.50 dB, mean ± standard deviation), and quality was visually inspected (12/17 usable for diagnosis). Recording was not supported in 9 cases. This was due to the browser's insufficient support for the flash light API. The app received a System Usability Scale score of 82 ± 9, which is above the 90th percentile. Overall, browser flash light support is the main limiting factor for broad device support. Thus, browser-based PPG is not yet widely applicable, although most participants feel comfortable with the recording itself. The utilization of the user-facing camera might represent a more promising approach. This study contributes to the development of low-barrier, user-friendly, installation-free smartphone signal acquisition. This enables profound, comprehensive data collection for research and clinical practice.Clinical relevance - WebPPG offers low-barrier remote diagnostic capabilities without the need for app installation
Created from Fastlane, Scopus look-up
Keywords: Heart rate; Limiting; Cameras; Photoplethysmography; Libraries; Recording; Usability